Bureaucratic models - Lasso Molina, Jorge (2021)
One of the main paradigms of Public Administration is the development and structure of a bureaucratic model (bureaucracy) that is capable of fulfilling its role in the cycle of public policies, understood as a kind of definition. of what the State decides or not to do. The effects of the political cycle, the evolution of needs and the permanent changes of actors are examples of environmental factors that affect the bureaucracy both in its structure and in its operation, reasons for which it is necessary to determine a base of particularities that guide and allow giving conceptual and operational coherence to the model. Based on the bibliographic review on the subject, three levels of characteristics have been structured, which, acting interdependently, allow the bureaucratic model to become a tool that supports and encourages development reflected in the successful implementation of public policies. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/1410